Glycoprotein recognition mediates attachment of Plasmodium chabaudi to mouse erythrocytes. - Rodriguez, M H (1987)
The interaction between Plasmodium falciparum merozoites and human erythrocytes is mediated by specific parasite proteins and sialoglycoproteins (SGPs) on the surface of the host cell. To investigate whether a similar mechanism functions in rodent malaria, a series of experiments was performed to identify the proteins involved in the interaction of Plasmodium chabaudi parasites and mouse erythrocytes. Labeled parasite proteins incubated with purified mouse SGP bound specifically to glycoprotein 2.1. Two parasite proteins (72 and 126 kilodaltons [kDa]) were coprecipitated with antibody directed to mouse erythrocyte membrane proteins. The lower band (72 kDa) as well as a band of 105 kDa were also observed to bind to N-acetyl-D-galactosamine affinity columns, suggesting a carbohydrate component in the binding of these parasites to erythrocytes. These experiments indicate that P. chabaudi possesses specific proteins which recognized SGP on the surface of murine erythrocytes in a manner similar to that of the merozoites of P. falciparum. Thus P. chabaudi in mice may provide an in vivo model of the human parasite for testing ways to inhibit merozoite recognition and invasion of host cells.